A Revision of the Weevil Genus Phyxelis Schönherr 1843 (Coleoptera: Curculionidae; Entiminae; Tropiphorini) in North America. Issue 5 (10th September 2018) - Anderson, Robert S
Abstract: The genus Phyxelis Schönherr is revised for North America. In total, three species are known including the widespread Eastern United States and Canada species Phyxelis rigidus (Say) and two new species described herein as follows: Phyxelis sus Anderson, n. sp. (type locality Claiborne Parish, LA) and Phyxelis carltoni Anderson, n. sp. (type locality Mount Magazine State Park, Logan County, AR). Species are described or redescribed, natural history information is summarized, and a listing of locality data from all specimens examined is included and mapped. A key is provided to the species of the genus. All species are represented by habitus images and images of taxonomically significant structures. Species of Phyxelis share a similar ramose/papillate scale form with species of the genera Paranametis Burke and Leptopinara O'Brien that is unique among North American Tropiphorini.